Analysis of prodromal symptoms and need for short-term prophylaxis in angioedema patients under long-term prophylaxis - Robin Lochbaum; Thomas K. Hoffmann; Jens Greve; Janina Hahn (Orphanet Journal of Rare Diseases)
Abstract Background Patients with hereditary angioedema (HAE) experience recurrent, unpredictable episodes of edema. These swellings are often preceded by prodromal symptoms. HAE management includes acute treatment, long-term prophylaxis (LTP), and short-term prophylaxis (STP) before procedures with a risk of swelling. The effects of LTP on prodromal symptoms and the necessity for STP in patients on LTP remain unclear. Methods A questionnaire-based study involving HAE and AAE patients receiving LTP was conducted. Changes in prodromal symptoms and the incidence of procedures with an increased risk of swelling, including surgeries, dental procedures, and endoscopies were assessed. Results A total of 26 patients were included in the study. Among them, 18 experienced zero to three attacks since starting LTP. Abdominal attacks constituted 60% of all attacks, followed by swellings of the extremities and head and neck. The most frequently reported trigger factors were stress and mechanical stimuli, followed by infections. 9 patients reported surgical procedures, with 8 using STP. Of these, 4 experienced breakthrough attacks, including one laryngeal attack. 105 dental procedures were reported, with STP used for only one. Only one angioedema attack occurred after an intervention without STP. For endoscopies, 7 procedures were reported, 3 of which were performed under STP. Two abdominal attacks were reported by the same patient, both without prior STP. Prodromal symptoms remained consistent in type but varied in intensity and frequency under LTP. Conclusions For dental procedures, the mandatory use of STP in HAE patients on effective LTP should be reconsidered, provided acute treatment is available and other trigger factors are absent.